2006
DOI: 10.1080/01446190500249510
|View full text |Cite
|
Sign up to set email alerts
|

Assessing how organizations approach the maintenance management of listed buildings

Abstract: Preventative maintenance has been identified as a key intervention in protecting built cultural heritage. How organizations approach the maintenance management of listed buildings in their care is explored using a framework which integrates best practice from the general maintenance management and conservation sectors. At present both heritage and non-heritage organizations are falling short of a best-practice approach. Although there is increasing awareness among heritage organizations about the importance of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 3 publications
1
11
0
Order By: Relevance
“…For this reason, a large-scale survey is recommended. This finding is, however, consistent with the work ofDann et al (2006) who investigated how heritage organisations approach maintenance management of listed buildings. Dann et al found that, although there is increasing awareness about the importance of maintenance, these organisations lack a systematic and integrated approach to maintenance.…”
supporting
confidence: 92%
“…For this reason, a large-scale survey is recommended. This finding is, however, consistent with the work ofDann et al (2006) who investigated how heritage organisations approach maintenance management of listed buildings. Dann et al found that, although there is increasing awareness about the importance of maintenance, these organisations lack a systematic and integrated approach to maintenance.…”
supporting
confidence: 92%
“…For the specific purposes of planning and programming CRM (conservation repair and maintenance) activities, information and documentation in this format does not facilitate efficient analysis, planning and decision making. Despite these inherent limitations, 'the use of textual documentation for the recording [and managing] of condition survey data…appears to be the norm in heritage sectors' [32]. This paper investigates the BIM concepts of component based parametric modelling, the application of data parameters to produce structured data sets, and BIM information management processes for the CRM of heritage assets.…”
Section: Producing Structured Datasets For the Hbim Asset Information Modela Framework Of Conservation Data Parametersmentioning
confidence: 99%
“…Buildings are usually designed with a certain amount of esthetics and cultural significance. The esthetics of a building can represent the corporate image or identity of an organization (Vijverberg, 2000) while cultural significance may contain historical value that requires preservation (Dann et al, 2006). While esthetics and cultural significance can represent the image of the organization, it might not warrant a high priority in the maintenance planning (Smith and Stewart, 2007).…”
Section: Social Factorsmentioning
confidence: 99%